(untitled) (Journal of actual problems of jurisprudence, 2019)
The article is intended to analyze the impact of lobbying on lawmaking, as one of the subjective factors of lawmaking. In lobbying law, lobbying is an activity that affects the legislative process to introduce their interests into the regulatory legal act of certain social groups. The purpose of the research is to determine the role of lobbying in the implementation of lawmaking and justify the need for its professional regulation. The scientific significance of the work outlines the necessity of lobbying methods in the world legal practice, its positive and negative aspects, and the need to create a unified system of lobbyist legal regulation. Research methods are comparison, analysis, synthesis, induction, deduction, statistical method, dialectical method, historical. As a result of the research, the lobby is an integral, very important institute of law. It was concluded that in Kazakhstan it is necessary to define the goals, possible methods and forms of the lobbying activity, taking into account the best international experience in creating a unique, effective system of legal regulation of lobbyist activity. Lobbying is a factor that influences the creation of legislative texts, as well as the formation and adoption of the text of the law, which is an effective tool that promotes common understanding and broadening democratic principles in the life of the state, reaching a common agreement on draft laws. In the article the effect of lobbying on the effectiveness of lawmaking, its useful results are determined. Key words: lawmaking, lobbying, legal act, bill, legal regulation, subjective factors of lawmaking.